Sistem Pendukung Keputusan Kenaikan Jabatan Pegawai Negeri Sipil Pada Pusat Penelitian Dan Pengembangan Minyak Dan Gas Bumi Lemigas Kementerian ESDM Dengan Metode Profile Macthing - . Harriyansah; Taufik Baidawi (Universitas Bina Sarana Informatika, 2018)
Filling vacant positions in the promotion process is often run into trouble because the candidate who can occupy that position by matching employee profiles and the profile is less well defined positions. Methods to support the decision to increase this position is the method of matching profiles. This research was conducted by finding the weight values for each criterion, such as aspects of intellectual capacity, aspects of the work attitude, behavioral aspects and aspects of intelligence work and then look for the value of core factors and secondary factors, the total value and the final value is the value of the ranking. Profile Matching method used here to get an assessment of each prospective employee will be raised position. The smaller the value gap is generated then the weight of large value, which means that employees have greater opportunities to occupy these positions. The results of this study to determine the calculation regarding the selection of eligible employees into office with a matching profile method.